Importance of Initial Development Stages of CASWAT-G Surface Ropeway - Baral, Lok Bahadur; Nalmpantis, Dimitrios; Amatya, Vishwa Prasanna; Dura, Hari Bahadur; Sah, Chandan; Poudyal, Khem Narayan (Amrit Research Journal, 2024)
This research paper details the foundational development of the Circulating Cable Supported Up-down Walking Technology using Gravity (CASWAT-G) Surface Ropeway (CSR), a pioneering transportation system designed to harness Gravitational Potential Energy (GPE) and Leg Muscle Efforted Energy (LMEE) for movement in mountainous regions. Developed initially in Nepal in 2005, CSR represents a unique, sustainable alternative to conventional transportation by utilizing naturally occurring energy sources, minimizing the need for external power inputs. The CSR system draws inspiration from Rock Climbing (RC), funiculars, ski lifts, and gravity ropeway systems. A prototype constructed from accessible materials such as Bicycle Wheels (BW) and rock-climbing ropes was initially tested with promising results that demonstrated smooth up-and-down movement with minimal effort. Subsequent research focused on establishing a theoretical basis for CSR, drawing comparisons to related systems, and analyzing the forces involved in its operation. Through graphical representation, the study examines acceleration and deceleration in the CSR system across various mass ratios and inclines, helping to validate CSR’s functionality and user safety. Results indicate that CSR efficiently combines GPE from descending users with LMEE from ascending users, facilitating a self-sustaining cycle of motion. These findings underscore CSR’s potential as an eco-friendly transport solution, particularly suited for rugged terrains where other systems may be cost-prohibitive or environmentally invasive. The successful prototype tests and theoretical validations have laid the groundwork for CSR’s development, with future implementations planned for public transport and tourism in mountainous regions, offering an innovative, low-impact, and accessible transportation option.